The Clinical Investigation of Disparity of Utility Values Associated with Gallstone Disease: A Pilot Study - Chung-Te Hsu; Yi Liao; Jorn-Hon Liu; Tao-Hsin Tung (Gastroenterology Research and Practice)
Purpose. The utility evaluation was an effective method to incorporate all of the contributing variables for multiple diseases into one outcome measure. A cross-sectional study was conducted to assess the utility values associated with varying states of gallstone disease among outpatient clinics participants at a teaching hospital in Taipei, Taiwan. Methods. The utility values were measured by using time trade-off method. A total of 120 outpatient clinics participants (30 subjects with no gallstone disease, 30 subjects with single stone, 30 subjects with multiple stones, and 30 subjects with cholecystectomy) evaluated utility values from January 1, 2006 to December 31, 2006. The diagnosis of gallstone disease was performed by a panel of specialists using ultrasound sonography. Results. The overall mean utility value was 0.89±0.13 (95% CI: 0.87–0.91) indicating that study participants were willing to trade about 11% (95% CI: 9–13%) of their remaining life in return for being free of gallstone disease perpetually. The significant associated factors of utility values based on the multiple linear regression analysis were older age and different degrees of gallstone disease. Conclusion. Our results found that in addition to older age, multiple stones and cholecystectomy could influence utility values from the patient’s preference-based viewpoint.